"What do you expect from physiotherapy?": a conversation analytic approach to goal setting in physiotherapy - Schoeb Mezzanotte, Veronika (2014)
Professional practice guidelines direct health care professionals to include patients in the decision-making process and to establish collaboration for therapeutic goal setting. Currently, little is known about the interaction between patients and professionals during this process. The aim of this study is to shed light on goal setting practices in physiotherapy.